Pengaruh Kompensasi Dan Motivasi Terhadap Kepuasan Dan Kinerja Karyawan Pada Hotel Bakung’s Beach Cottages Kuta-Bali - Astuti, Ni Ketut Ayu Juli; Sudharma, I Nyoman (E-Jurnal Manajemen, 2013)
This study aimed to determine the effect of compensation and motivation on job satisfaction and employee performance . The study was conducted at Bakung’s Beach Cottages with the object of this study is compensation, motivation, job satisfaction and employee performance in Bakung’s Beach Cottages Kuta-Bali. Population as well as samples in this study were all employees who worked at Bakung’s Beach Cottages number 59. The results obtained in this study that are: 1) compensation have significant positive impact on job satisfaction , 2) motivation have significant positive impact on job satisfaction , 3) compensation have significant positive impact on employee performance , 4) motivation have significant positive impact on employee performance , 5) job satisfaction have significant positive impact on employee performance . Keywords: compensation, motivation, job satisfaction, performance